An Obstetrics Index for the Assessment of Risk Levels of “High Risk Pregnancy” Groups - M. Sinan Beksaç; Emine Aydın; Mert Tuğral; Ergün Karaağaoğlu (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To validate the usability of “Beksaç Obstetrics Index” (BOI/BOIp) in the evaluation of different high risk pregnancy groups.